2014
DOI: 10.11144/javeriana.ie17-1.fcrm
|View full text |Cite
|
Sign up to set email alerts
|

Fadiga clinicamente relevante em mulheres com câncer de mama: prevalência e fatores associados

Abstract: Introducción: La fatiga es un síntoma frecuente en pacientes con cáncer. Objetivo: Examinarla prevalencia y los predictores independientes de la fatiga en las mujeres concáncer de mama. Material e método: Se trata de un estudio transversal con una muestrano probabilística de 163 pacientes en acompañamiento ambulatorio. La fatiga fueevaluada por la Escala de Fatiga de Piper. Resultados: La fatiga clínicamente relevante(puntuación ≥ 4) estuvo presente en el 31,9 % de la muestra y la intensidad media fue de6 (DP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
2
0
2
Order By: Relevance
“…Another study that evaluated women with breast cancer identified clinically relevant fatigue (> 4 intensity) in 31.9% of women, and this symptom was associated with pain and depression (14) . In patients with colorectal cancer, fatigue occurred in 26.8% and predictors were: depression, impaired functioning and sleep disorders (15) .…”
Section: Introductionmentioning
confidence: 99%
“…Another study that evaluated women with breast cancer identified clinically relevant fatigue (> 4 intensity) in 31.9% of women, and this symptom was associated with pain and depression (14) . In patients with colorectal cancer, fatigue occurred in 26.8% and predictors were: depression, impaired functioning and sleep disorders (15) .…”
Section: Introductionmentioning
confidence: 99%
“…Outro dado relevante foi que pacientes submetidas a um maior número de sessões de radioterapia e intervalos menores entre a realização da última aplicação da radioterapia e a mensuração do sintoma relataram maior nível de fadiga. 8,13 A detecção precoce deste sintoma, usando escalas adequadas, é relevante para propor tratamentos adequados e alcançar melhores condições clínicas, adesão e continuidade do tratamento. Porém, o profissional de saúde teve ter o conhecimento que raramente a fadiga surge como sintoma isolado, está frequentemente associado a outros sintomas tais como: dor, depressão, alterações de sono, anemia e caquexia, entre outros, constituindo assim um Pictograma de fadiga durante o uso de quimioterápico no tratamento do câncer de mama | 14 Rev.…”
Section: Introductionunclassified
“…Assim, a conduta terapêutica da fadiga requer que o acompanhamento inclua a percepção e a investigação de outros sintomas. 8,10,13…”
Section: Introductionunclassified
“…Thus, daily physical activities such as walking, exercising, cleaning the house, cooking, and even eating can become major challenges for patients with fatigue. Limitations from cancer and its treatment are also associated with a progressive loss of muscle mask, which decreases muscle strength and reduces the ability of patients to perform simple tasks of daily routine, intensifying the symptoms and leading to inability (31) .…”
Section: Discussionmentioning
confidence: 99%